The Heptameron, or, Tales and novels of Marguerite, Queen of Navarre / tr. by Arthur Machen, with an introduction. - Marguerite, Queen, consort of Henry II, King of Navarre, 1492-1549. (Tufts University. Tisch Library., 2016)
1 online resource (xx, 392 pages).; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.